الفكر السياسي في العصر الحديث - بالعجال,حمزة; باسو,محمد الطاهر (University of Eloued جامعة الوادي, 2024)
ملخص: لا شك أن الفيلسوف والمفكر الفرنسي "جون جاك روسو" من الفلاسفة المتميزين، إذ تختلف عبقريته عن غيره من الفلاسفة الذين تغنوا بالإنسان الطبيعي بصوره في صورة الانسان الهاني السعيد، الذي لا يعرف القيود والحواجز ويتصرف بتلقائية وحرية، فقد تركت أعماله وأفكاره بصمة في الفكر السياسي، باعتباره فيلسوف الطبيعية هذه الاخيرة أساس الخير والجمال، ومن خلال دعوته للمجتمع الطبيعي القائم على مبادئ الحرية والعدالة والمساواة هي أسس كلها قوام للمجتمع المدني المتحضر، وقد ناضل "روسو" من أجل ترسيخ حقوق الانسان من خلال نظرياته السياسية والتي جعلها كأساس لإصلاح المجتمع، هذه النظريات السياسية تنطلق من موقفه من خلال العقد الاجتماعي بين الحاكم والرعية، فهو الميثاق الذي يربطهم، وقد كان معروف قبل روسو إلا أنه كانت له بصماته الخاصة فيه، فهو لم يكن معدا ، بل ناضل فكره السياسي لصالح الفرد وحقوقه وكذا رفع من قيمة المجتمع، وذلك برفضه لكل تغير اجتماعي على حساب الأفراد، إذ توصل في النهاية الى أن أفضل نظام حكم قائم هو الديمقراطية كونها صالحة لكل اجتماع انساني، فنظريته شكلت تحولا جذريا في المفاهيم السياسية، وأدت إلى ميلاد ثورات وقوانين جديدة قلبت الموازين القديمة السائدة في أوربا خاصة و العالم عامة. وبهذا نستطيع القول ان نظرية روسو السياسة متكاملة ومع انها تشترك مع غيرها من النظريات إلا أنها تشكل مذهبًا سياسيا منفردا. . Summary: There is no doubt that the French philosopher and thinker Jean-Jacques Rousseau is one of the distinguished philosophers, as his genius differs from other philosophers who praised the natural human being by portraying him in the form of the happy, carefree human being, who does not know restrictions and barriers and acts spontaneously and freely. His works and ideas left an imprint on political thought, as he the philosopher of nature, the latter the basis of goodness and beauty and through his call for a natural society based on the principles of freedom, justice and equality are the foundations of civilized civil society. Rousseau struggled to establish human rights through his political theories, which he made a basis for reforming society. These political theories take off from his position on the social contract between the ruler and the subjects; it is the charter that binds them. It was known before Rousseau, but he had his own mark on it. He was not prepared. Rather, his political thought fought in favor of the individual and his rights, as well as raising the value of society, by rejecting all change. Social at the expense of individuals, as he ultimately concluded that the best existing system of government is democracy, as it is suitable for every human meeting. His theory constituted a radical shift in political concepts, and led to the birth of revolutions and new laws that changed the balance. The old prevailing in Europe in particular and the world in general. Thus, you can say that Rousseau's theory of politics is integrated, even though it has similarities with other theories However; it constitutes a single political doctrine.
جون جاك روسو أنموذجا
Keywords: الفكر السياسي; العصر الحديث; جون جاك روسو; politicalthought; modern era; Jean-Jacques Rousseau